English Teachers’ Conceptions of Formative Assessment in Online Teaching - Lisyowati, Wanda; Wiyaka, Wiyaka; Prastikawati, Entika Fani (Universitas Negeri Semarang, 2021)
Formative assessment is one type of assessment that is commonly implemented in teaching and learning. However, to carry out a formative assessment, teachers need to adjust the conceptions of formative assessment in the online teaching and learning environment. This descriptive qualitative study aimed to determine the English teacher's conceptions of formative assessment in online teaching and learning. To gather the data, the writers used a closed-questionnaire and semi- structured interview. Furthermore, two English teachers participated as the sample of this study. These two English teachers were selected based on several predetermined conditions; teaching experience and educational background. The result of this study shows that both English teachers have a good conception of formative assessment in online teaching. They consider that the application of formative assessments in the online classroom is easy and does not need complicated requirements in its implementation. In addition, formative assessment can help English teachers monitor the progress of their students so that they can prepare better future lesson plans according to the conditions of their students in the online teaching and learning process.